Menakar Tingkat Kepuasan Wisatawan: Kunci Keberhasilan Pengembangan Amenitas Pantai Slili sebagai Destinasi Wisata Bahari - Masjhoer, Jussac Maulana; Rukmini A.R.; Mokodongan, Trisagia (CV. Kurnia Grup, 2024)
Tourist satisfaction serves as a crucial indicator of successful tourism development. It is imperative for managers to periodically assess the tourism facilities to gauge the destinations' quality through the visitors' perspective. Therefore, this study endeavors to assess the level of tourist satisfaction regarding the tourism facilities at Slili Beach. A total of 100 respondents participated in the questionnaire, which was subsequently analyzed using descriptive quantitative methods. The findings revealed that tourists exhibited dissatisfaction with public toilet facilities and trash bins, with percentages of 42.25% and 38.75%, respectively. Conversely, tourists expressed contentment with rest area facilities, parking, and places of worship, with percentages of 51.34%, 47.71%, and 45.5%, respectively. However, the availability of disabled facilities left 61.5% of tourists significantly dissatisfied. These findings underscore the need for managers to address the discrepancies between tourists' expectations and the actual offerings at Slili Beach. Consequently, there is a pressing need for managers to enhance the quality of tourism facilities to ensure and bolster tourist satisfaction. Furthermore, future research endeavors could explore the correlation between tourist satisfaction and the inclination to revisit, providing managers with compelling reasons to continually improve the quality of facilities at marine tourism destinations.